Methylation of HOXA9 and ISL1 predicts patient outcome in high-grade non-invasive bladder cancer - Kitchen, Mark O.; Bryan, Richard T.; Haworth, Kim E.; Emes, Richard D.; Luscombe, Christopher; Gommersall, Lyndon; Cheng, K.K.; Zeegers, Maurice P.; James, Nicholas D.; Devall, Adam J.; Fryer, Anthony A.; Farrell, William E. (Public Library of Science, 2015)
Introduction